Lake-level variations and tides in Lago Argentino, Patagonia: Insights from pressure tide gauge records - Richter, Andreas Jorg (2016)
Based on precise pressure tide gauge observations lake-level records are derived for two sites in Lago Argentino, southern Patagonia, of 2.5 and 1 years of duration. Applying the tools of time series analysis, the principal processes affecting the lake level are identified and quantified. Lake-level changes reflecting variations in lake volume are dominated by a seasonal cycle of 1.2 m in amplitude. Lakevolume changes occur in addition with a daily period in response to melt water influx from surrounding glaciers. Sporadic lake-volume jumps are caused by bursting of the ice dam of Perito Moreno glacier. Water movements in Lago Argentino are dominated by surface seiches reaching 20 cm in amplitude. Lake tides reach a maximum amplitude of 3 mm. The comparison of the tidal signal extracted from the lake-level observations with a model composed of the contributions of body tide and ocean tidal loading indicates a phase shift of 23° which is most likely explained by an 1 hour phase lag of global ocean tide models in the region of the highly fragmented Pacific coast. The comparison of the obtained results with those of a previous study of Lago Fagnano, Tierra del Fuego, allows to relate differences in the hydrological and hydrodynamic processes between both lakes to morphological properties. This leads to a tentative prediction of the lake-level variability to be expected from other great Patagonian lakes. The presented geodetic results shall serve as a starting point for a detailed limnological investigation of these aquatic ecosystems.